(untitled) (International Journal of Studies in Nursing, 2021)
Background: Cardiovascular diseases are the second leading cause of death in the top ten leading causes of death in 2018 in Taiwan, and coronary artery disease is one of the main causes. Aim: To compare whether there are differences in patient knowledge, anxiety, and satisfaction between the utilization of patient decision aid for cardiac catheterization and routine health education. Subject and methods: Between July 2020 and September 2020, subjects were recruited in the clinics of the Department of Cardiology in a Veterans hospital in northern Taiwan. An experimental design was used for the study. Subjects were divided into two different education tool groups by randomization table. Subjects filled out the questionnaires before and after the education. Result: The patient knowledge before and after education in the RC group was improved by 2.30 points, and SDM group increased by 1.50 points (p-value<0.05). The score of anxiety decreased by 0.41 points in the RC group after the education, and the score of anxiety decreased by 0.33 points in the SDM group. The levels of satisfaction of the SDM group were all higher than the RC group, but the satisfaction score for the duration of education in both groups was relatively low. Conclusion: Regardless of the standard or SDM education model, the knowledge level of patients can be improved, and there was a statistically significant difference (P<0.05). The anxiety of patients in both groups was reduced. The satisfactions of education in the SDM group were better than those of the RC group. The duration of education was the item with low satisfaction for both groups. Recommendations: Both methods of education can help patients increase their knowledge. The establishment of manpower responsible for education. Allowing patients to receive education before the examination can decrease anxiety and has clinical benefits.